Structural alterations in the seminiferous tubules of rats treated with immunosuppressor tacrolimus - Caneguim, Breno H.; Cerri, Paulo Sérgio [UNESP]; Spolidório, Luis Carlos [UNESP]; Miraglia, Sandra M.; Cerri, Estela Sasso [UNESP] (Biomed Central Ltd., 2009)
Background: Tacrolimus (FK-506) is an immunosuppressant that binds to a specific immunophilin, resulting in the suppression of the cellular immune response during transplant rejection. Except for some alterations in the spermatozoa, testicular morphological alterations have not been described in rats treated with tacrolimus. In the present study, we purpose to evaluate if the treatment with tacrolimus at long term of follow-up interferes in the integrity of the seminiferous tubules.Methods: Rats aging 42-day-old received daily subcutaneous injections of 1 mg/kg/day of tacrolimus during 30 (T-30) and 60 (T-60) days; the rats from control groups (C-30 and C-60) received saline solution. The left testes were fixed in 4% formaldehyde and embedded in glycol methacrylate for morphological and morphometric analyses while right testes were fixed in Bouin's liquid and embedded in paraffin for detection of cell death by the TUNEL method. The epithelial and total tubular areas as well as the stages of the seminiferous epithelium and the number of spermatocytes, spermatids and Sertoli cells (SC) per tubule were obtained.Results: In the treated groups, seminiferous tubules irregularly outlined showed disarranged cellular layers and loss of germ cells probably due to cell death, which was revealed by TUNEL method. In addition to germ cells, structural alterations in the SC and folding of the peritubular tissue were usually observed. The morphometric results revealed significant decrease in the number of SC, spermatocytes, spermatids and significant reduction in the epithelial and total tubular areas.Conclusion: Tacrolimus induces significant histopathological disorders in the seminiferous tubules, resulting in spermatogenic damage and reduction in the number of Sertoli cells. A careful evaluation of the peritubular components will be necessary to clarify if these alterations are related to the effect of FK-506 on the peritubular tissue.